Biochemodynamic Features of Metal Ions Bound by Micro- and Nano-Plastics in Aquatic Media - Town, Raewyn M.; van Leeuwen, Herman P.; Blust, Ronny (Frontiers in Chemistry, 2018)
A simple model, based on spherical geometry, is applied to the description of release kinetics of metal species from nano- and micro- plastic particles. Compiled literature data show that the effective diffusion coefficients, Deff, for metal species within plastic polymer bodies are many orders of magnitude lower than those applicable for metal ions in bulk aqueous media. Consequently, diffusion of metal ions in the aqueous medium is much faster than that within the body of the plastic particle. So long as the rate of dissociation of any inner-sphere metal complexes is greater than the rate of diffusion within the particle body, the latter process is the limiting step in the overall release kinetics of metal species that are sorbed within the body of the plastic particle. Metal ions that are sorbed at the very particle/medium interface and/or associated with surface-sorbed ligands do not need to traverse the particle body and thus in the diffusion-limiting case, their rate of release will correspond to the rate of diffusion in the aqueous medium. Irrespective of the intraparticulate metal speciation, for a given diffusion coefficient, the proportion of metal species released from plastic particles within a given time frame increases dramatically as the size of the particle decreases. The ensuing consequences for the chemodynamics and bioavailability of metal species associated with plastic micro- and nanoparticles in aquatic systems are discussed and illustrated with practical examples.